High-grade renal injuries are often isolated in sports-related trauma. Issue 7 (July 2015) - Patel, Darshan P.; Redshaw, Jeffrey D.; Breyer, Benjamin N.; Smith, Thomas G.; Erickson, Bradley A.; Majercik, Sarah D.; Gaither, Thomas W.; Craig, James R.; Gardner, Scott; Presson, Angela P.; Zhang, Chong; Hotaling, James M.; et al.
Abstract Introduction Most high-grade renal injuries (American Association for Surgery of Trauma (AAST) grades III–V) result from motor vehicle collisions associated with numerous concomitant injuries. Sports-related blunt renal injury tends to have a different mechanism, a solitary blow to the flank. We hypothesized that high-grade renal injury is often isolated in sports-related renal trauma. Material and methods We identified patients with AAST grades III–V blunt renal injuries from four level 1 trauma centres across the United States between 1/2005 and 1/2014. Patients were divided into "Sport" or "Non-sport" related groups. Outcomes included rates of hypotension (systolic blood pressure <90 mm Hg), tachycardia (>110 bpm), concomitant abdominal injury, and procedural/surgical intervention between sports and non-sports related injury. Results 320 patients met study criteria. 18% (59) were sports-related injuries with the most common mechanisms being skiing, snowboarding and contact sports (25%, 25%, and 24%, respectively). Median age was 24 years for sports and 30 years for non-sports related renal injuries (p = 0.049). Males were more commonly involved in sports related injuries (85% vs. 72%, p = 0.011). Median injury severity score was lower for sports related injuries (10 vs. 27, p < 0.001). There was no difference in renal abbreviated injury scale scores. Sports related trauma was more likely to be isolated without other significant injury (69% vs. 39% (p < 0.001)). Haemodynamic instability was present in 40% and 51% of sports and non-sports renal injuries (p = 0.30). Sports injuries had lower transfusion (7% vs. 47%, p < 0.001) and lower mortality rates (0% vs. 6%, p = 0.004). There was no difference in renal-specific procedural interventions between the two groups (17% sports vs. 18% non-sports, p = 0.95). Conclusions High-grade sports-related blunt renal trauma is more likely to occur in isolation without other abdominal or thoracic injuries and clinicians must have a high suspicion of renal injury with significant blows to the flank during sports activities.